1997
DOI: 10.1086/514008
|View full text |Cite
|
Sign up to set email alerts
|

PostoperativeSerratia marcescensWound Infections Traced to an Out‐of‐Hospital Source

Abstract: From 25 August to 28 September 1994, 7 cardiovascular surgery (CVS) patients at a California hospital acquired postoperative Serratia marcescens infections, and 1 died. To identify the outbreak source, a cohort study was done of all 55 adults who underwent CVS at the hospital during the outbreak. Specimens from the hospital environment and from hands of selected staff were cultured. S. marcescens isolates were compared using restriction-endonuclease analysis and pulsed-field gel electrophoresis. Several risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 10 publications
0
58
0
4
Order By: Relevance
“…In addition, several studies of HCP hand carriage have been performed during outbreaks in efforts to detect a potential point source. Outbreaks of Pseudomonas aeruginosa [5,6], extended spectrum β-lactamase-producing Klebsiella pneumoniae [7], and Serratia marcescens [8] have been linked to artificial nails worn by HCP, and molecular epidemiology has confirmed transmission to infants. However, all 4 sites in this current study banned HCP from wearing artificial nails.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies of HCP hand carriage have been performed during outbreaks in efforts to detect a potential point source. Outbreaks of Pseudomonas aeruginosa [5,6], extended spectrum β-lactamase-producing Klebsiella pneumoniae [7], and Serratia marcescens [8] have been linked to artificial nails worn by HCP, and molecular epidemiology has confirmed transmission to infants. However, all 4 sites in this current study banned HCP from wearing artificial nails.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an outbreak of postoperative S. marcescens wound infections was traced to a contaminated jar of exfoliant cream in a nurse's home. 167 An investigation suggested that the organism was transmitted to patients via the hands of the nurse, who wore artificial fingernails. In another outbreak, Malassezia pachydermatis was probably transmitted from a nurse's pet dogs to infants in an intensive care nursery via the hands of the nurse.…”
Section: Cross-transmission Of Organisms By Contaminated Handsmentioning
confidence: 99%
“…HCWs wearing artificial nails have also been epidemiologically implicated in several other outbreaks of infection caused by Gram-negative bacilli or yeast. 159,167,977 In a recent study, multiple logistic regression analysis showed the association of an outbreak of extended-spectrum beta-lactamase-producing K. pneumoniae in a neonatal ICU resulting from exposure to an HCW wearing artificial fingernails. 155 A cluster of five cases of S. marcescens bacteraemia in haemodialysis was associated with a nurse who used an artificial fingernail to open a vial of heparin that was mixed to make a flush solution.…”
Section: Fingernails and Artificial Nailsmentioning
confidence: 99%
See 1 more Smart Citation
“…marcescens is now recognized as a prominent opportunistic pathogen causing significant outbreaks of nosocomial infections of various severities, such as urinary tract infections (UTIs) (5,15,16,20,28), respiratory tract infections (28), bacteremia (12,16,18,28,34), conjunctivitis (11), endocarditis (6), meningitis (34), and wound infections (18,28). In recent years, outbreaks associated with extended-spectrum ␤-lactamase-producing (9,17) or imipenem-resistant (26) S. marcescens strains have emerged as an important infection control problem.…”
mentioning
confidence: 99%